A study of newly discovered lithics from earlier Stone Age deposits at Sterkfontein, Gauteng province, South Africa - Stratford, Dominic Justin (My University, 2009)
The need to expand the current lithic Plio-Pleistocene assemblages at Sterkfontein and to understand how these assemblages have been incorporated into the cave deposits is of key importance to archaeological research on the Oldowan and Early Acheulean of South Africa. The greater the archaeological sample size the more accurately inferences can be made regarding the behaviour and technological practices of local hominid groups. An accurate understanding of depositional processes influencing these assemblages allows inferences to be made regarding the post-depositional movement of elements within the assemblage. The first objective of this research is to expand the assemblages representing the earliest stone tool technologies found at Sterkfontein. The first assemblage researched here is the Dump 21 collection, a small number of artefacts found recently just south of the Sterkfontein Member 5 West breccia and the former Extension Site of John Robinson. This material had been removed from a cave deposit by lime miners and dumped where it was found. This dump may have been created up to a century ago and was concealed by vegetation. The technological attributes exhibited on the cores and flakes of Dump 21 were compared to the current Sterkfontein Early Acheulean of Member 5 West. Parallel patterns in core types and flaking patterns, as well as raw material utilisation, suggest analogous technological intention and therefore identical depositional origins. The second assemblage analysed here was excavated from the Name Chamber and yielded large quantities of quartz dominated small flaking debris. Comparisons of raw material profiles and technological attributes of artefacts <20mm in size indicate the Name Chamber artefacts originated within the Oldowan assemblage, with a large proportion of <10mm and some <20mm material being winnowed out of the Member 5 East Oldowan breccia at some stage. The second objective of this research was to more clearly understand the processes involved in the formation of the Name Chamber deposit, examination of the geology and stratigraphy of the Name Chamber was undertaken. Three depositional events have been isolated. The first deposit filled the existing Sterkfontein chambers prior to the opening of the caves to the surface. The second and third deposits have entered the Name Chamber through a shaft that appears to articulate with the deepest portions of the Member 5 East area of the site, forming fauna-rich talus slopes within the chamber. The changing internal structure of this shaft has influenced the size profile and destination of the sediments accumulated in the three current talus deposits fed by the shaft.